Quality, Affordability, and Perceived Value in Low-Income Consumers’ Daily Purchase Decisions - Ayuningtyas Putri Mumpuni; Wahyuni Rahmah; Abdul Syaban; Asraf Asraf (Research Horizon, 2026)
Low-income consumers are often viewed as highly price-sensitive market actors; however, recent studies suggest that their purchasing decisions are shaped not only by affordability considerations but also by product quality and perceived value. This study aims to examine the effects of perceived price affordability and perceived product quality on purchase decisions, as well as the mediating role of perceived product value among low-income consumers. A quantitative cross-sectional survey design was employed, involving 160 low-income consumers selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that perceived price affordability positively affects perceived product value and purchase decision. Perceived product quality also has positive effects on perceived product value and purchase decision, and represents the strongest predictor of perceived product value. Furthermore, perceived product value positively influences purchase decisions. Mediation analysis reveals that perceived product value significantly mediates the relationship between perceived product quality and purchase decision, but does not mediate the relationship between perceived price affordability and purchase decision. The findings suggest that low-income consumers evaluate affordability and quality simultaneously, with product quality playing a central role in value formation and purchasing decisions.